Tasty pride 75 recipes and stories from the queer food community - Szewczyk, Jesse (Clarkson Potter/Publishers, 2020)
"From the wildly popular, fiercly inclusive BuzzFeed cooking brand comes 75 recipes from prominent LGBTQ+ cooks and foodies"--